1992
DOI: 10.1542/peds.90.1.87
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of High Levels of Acute Behavioral Distress in Children and Adolescents Undergoing Routine Venipunctures

Abstract: While there is no question that children dislike needles, there are very little data available on the occurrence of high levels of distress experienced by children undergoing routine venipunctures. To provide some insight into this problem, trained observers evaluated distress in 223 different children and adolescents undergoing this procedure. An observational distress scale of 1 to 5 was developed; 1 = calm, 2 = timid/nervous, 3 = serious distress, but still under control, 4 = serious distress with loss of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(33 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…In another study evaluating distress related to needles during venipuncture, toddlers aged two and a half to 6 years and preadolescents aged 7–12 years were observed to be highly distressed (Humphrey et al, 1992). Considering that pain and fear are contributing factors for noncompliance with vaccinations (Russell and Harrison, 2015; Taddio et al, 2012), it is essential to implement and evaluate interventions to reduce such negative experiences and subsequently facilitate higher immunization coverage (Taddio et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In another study evaluating distress related to needles during venipuncture, toddlers aged two and a half to 6 years and preadolescents aged 7–12 years were observed to be highly distressed (Humphrey et al, 1992). Considering that pain and fear are contributing factors for noncompliance with vaccinations (Russell and Harrison, 2015; Taddio et al, 2012), it is essential to implement and evaluate interventions to reduce such negative experiences and subsequently facilitate higher immunization coverage (Taddio et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pain threshold research has suggested differing sensitivities and reactions to pain, based on sex differences 22 . However, researchers have shown that gender has no effect on pain intensity responses and behavioral responses to venipunctureand males were significantly more likely to underestimate pain and females were significantly more likely to overestimate pain.. [23][24][25][26] It was found out that from approximately 8 years of age, children (especially girls) gave significantly higher ratings of unpleasantness than sensory intensity of needle pain. Prior to the age of 8 years, children tended to give equivalent ratings of intensity and unpleasantness, with no evidence of a sex difference 5 The present study showed no impact of sex on pain perception.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety in response to distressing medical procedures, or procedural anxiety, is a common presenting issue in children under 6 years of age (Humphrey, Boon, van Linden van den Heuvell, & van de Wiel, 1992). A history of negative medical experiences during childhood is associated with increased anticipatory anxiety and greater distress during subsequent procedures (Bijttebier & Vertommen, 1998).…”
Section: Procedural Anxiety and Selective Mutismmentioning
confidence: 99%